The Effectiveness of an Interactive Manual according to the Expansionary Theory in Developing the Teaching Skills of the Classroom Teaching for the Practical Education Course in Faculties of Education - Arnoosy, Dihya Uweed Harbi Al (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present study tries to identify "The Effectiveness of an Interactive Manual according to the Expansionary Theory in Developing the Teaching Skills of the Classroom Teaching for the Practical Education Course in Faculties of Education". To achieve the aim of the present study, the researcher formulated the following null hypotheses: First Hypothesis: There is no statistically significant difference at the level of (0,05) between the scores of the experimental and control groups in the performance of teaching skills as a whole and measured in the observation form. The second hypothesis: There is no statistically significant difference at the level of (0,05) between the scores of the students in the control group in the pre-test and post-teaching skills. The current study aimed to know "designing an assistant guide for teachers of human specializations graduates of colleges of education for humanities." To achieve the goal of the current study, the researcher formulated the following zero hypotheses: 1- There is no statistically significant difference at the level of significance (0.05) between the average scores of students (teachers) in the teaching skills test before and after applying the proposed evidence according to the expansionary theory. 2- There is no statistically significant difference at the level of significance (0.05) between the average scores of students (teachers) in the observation card to perform teaching skills before and after applying the proposed evidence according to the expansionary theory. The results of the current research showed the superiority of the guide, and it has a positive effect on the teaching performance of teachers with their different specializations. The researchers came out with a set of conclusions, recommendations and proposals